Outcomes of mid-penile hypospadias repair using two different techniques - Abdelaziz Yehya; Mabrouk Akl; Mohamed Abd-Alrazek; Ibrahim ElSotohi; Mohamed Negm; Mohamed Abdel Aziz; Ibrahim Gamaan; Alsayed Othman (Wolters Kluwer Medknow Publications, 2019)
Introduction Several techniques have been reported for mid-penile hypospadias repair, including Snodgrass tubularized incised plate (TIP) and onlay island flap (OIF) procedures, which are two popular procedures. Aim of the work To compare the outcomes and complication rates for both TIP and OIF techniques. Patients and methods A prospective randomized study was conducted on 140 boys (age range, 1-6 years) with primary mid-penile hypospadias who underwent repair from June 2011 to December 2016 at our university hospitals. The patients were prospectively randomly divided into two equal groups: group A (n=70), underwent Snodgrass TIP urethroplasty, and group B (n=70), underwent OIF. Inclusion criteria only males with fresh mid penile hypospadias without ventral chordee from 1 to 6years old. Exclusion criteria were recurrent cases, presence of ventral chordee, parental refusal or children more than 6years of age. Outcomes were assessed in terms of success rates, operative time complication rates, and cosmetic appearance during follow-up. All children were subjected to full history taking, thorough clinical examination, and routine laboratory investigations (CBC, BT, CT, FBS, urinalysis, liver and renal profile), results were compiled and compared statistically. Results There were statistically significant differences between the two techniques regarding success rate, operative time incidence of complications and cosmetic results. Conclusion Both techniques are reliable and feasible for treatment of mid-penile hypospadias, but there was a statistically significant difference regarding operative time, complications, and cosmetic outcome with TIP procedure. So, the authors preferred it if suitable urethral plate is present.